2022
DOI: 10.3390/ijms23094578
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Conductive Hydrogels: Applications in the Field of Biomedicine

Abstract: The impact of COVID-19 has rendered medical technology an important factor to maintain social stability and economic increase, where biomedicine has experienced rapid development and played a crucial part in fighting off the pandemic. Conductive hydrogels (CHs) are three-dimensional (3D) structured gels with excellent electrical conductivity and biocompatibility, which are very suitable for biomedical applications. CHs can mimic innate tissue’s physical, chemical, and biological properties, which allows them t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 159 publications
(138 reference statements)
0
20
0
Order By: Relevance
“…In addition to avoiding damage to the human body, biocompatible hydrogels can even promote tissue regeneration. When the hydrogel material is applied to the wound, the 3D porous structure inside the hydrogel can carry bioactive components (such as biomolecules, proteins, and growth factors) to control and promote tissue regeneration and development [ 136 ].…”
Section: Design Strategies Of Composite Hydrogelsmentioning
confidence: 99%
“…In addition to avoiding damage to the human body, biocompatible hydrogels can even promote tissue regeneration. When the hydrogel material is applied to the wound, the 3D porous structure inside the hydrogel can carry bioactive components (such as biomolecules, proteins, and growth factors) to control and promote tissue regeneration and development [ 136 ].…”
Section: Design Strategies Of Composite Hydrogelsmentioning
confidence: 99%
“…Conductive hydrogels (CHs) bear resemblances to natural soft tissues and extracellular matrices (ECMs), , manifesting outstanding ductility and resilience. In addition to these characteristics, CHs possess highly desirable attributes such as biocompatibility, conductivity, and self-repair capabilities, rendering them particularly advantageous for applications in wearable strain sensors, notably in health monitoring and medical diagnosis, among other fields. The preparation of CHs typically involves employing the Schiff base reaction, , metal coordination, or multiple hydrogen bonds. , Furthermore, to enhance their conductive capacity, additives like Mexene, CNTs, rGOs, and AgNPs can be incorporated into the CHs. However, the fabrication of these multifunctional CHs often requires multiple synthesis steps and the addition of high-value fillers, leading to challenges in obtaining them with ease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that CH dressings possess similar conductivity and flexibility to skin, supporting wound repair and tissue regeneration. 13,14 Conductive hydrogels allow for the creation of a conductive pathway that guides cell adhesion and migration, promoting skin tissue regeneration. 9,15 CHs are commonly prepared by introducing conductive materials such as conductive polymers, graphene, or metal nanoparticles into the crosslinked hydrogel matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the conductivity of skin is about 10 –4 mS/cm and is sensitive to electrical signals, conductive hydrogels (CHs) have received attention due to their unique mechanical properties and conductivity. Studies have revealed that CH dressings possess similar conductivity and flexibility to skin, supporting wound repair and tissue regeneration. , Conductive hydrogels allow for the creation of a conductive pathway that guides cell adhesion and migration, promoting skin tissue regeneration. , CHs are commonly prepared by introducing conductive materials such as conductive polymers, graphene, or metal nanoparticles into the crosslinked hydrogel matrix . Poly­(3,4-ethylenedioxythiophene) (PEDOT), polyaniline (PANI), and polypyrrole (PPy) have been used to prepare CHs owing to their conductive properties. Moreover, the conductive polymers demonstrated antioxidant activity, which could support wound healing, based upon their conjugated backbone that can donate electrons for scavenging ROS. , For example, Zhu et al developed a single-electrode triboelectric nanogenerator-based e-skin patch to promote wound healing and sense motion using a polypyrrole/Pluronic F127 hydrogel as electrolytes.…”
Section: Introductionmentioning
confidence: 99%